Analysis of genetic diversity among the Indian bread wheat cultivars using microsatellite (SSR) markers - Sarkar, Sutapa; Singh, Anju M.; Chakraborti, Mridul; Singh, Santosh K.; Ahlawat, Arvind K.; Singh, Gyanendra P. (The Indian Journal of Genetics and Plant Breeding, 2016)
Genetic diversity among 35 wheat cultivars was evaluated using 30 polymorphic microsatellite (SSR) markers. Analysis of molecular diversity revealed moderate levels of polymorphism in the set of genotypes studied. Ninety alleles with an average of three alleles per locus were detected. The allelic polymorphism information content (PIC) value ranged from 0.06 to 0.76 with an average of 0.45. The primers like Xgwm294, Xgwm146, Xgwm455, Xgwm497, Xgwm136 and Xgwm132 could be considered particularly informative, as they revealed four or more alleles per locus and displayed high PIC values.Ten rare and three unique alleles were recorded. The most closely related cultivars were ‘Raj3765’ and ‘HD 2402’ displaying the lowest dissimilarity index, whereas highest genetic distance was observed between ‘Pissi Local’and‘HB 208’.The land race ‘Pissi Local’ revealed very high genetic distance with most of the cultivars where the dissimilarity indices ranged from 0.42-0.74. Three major clusters comprising 13, 12 and 10 genotypes were formed. Despite the presence of variability among the different Indian cultivars the varieties developed at various institutes during different time periods clustered together indicating the use of common genotypes in the pedigree